Pengaruh Green Innovation dan Green Intellectual Capital terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Moderasi - Clarissa Tonay; Etty Murwaningsari (Jurnal Bisnis dan Akuntansi, 2022)
This study examines the effect of green innovation and green intellectual capital on firm value, as well as the effect of firm size on the memorization of green innovation and green intellectual capital on firm value. This study used non-financial sector data listed on the Indonesia Stock Exchange (IDX) for the 2020-2021 period. Furthermore, this study used a purposive sampling for data sampling and multiple regression models for data analysis method. The green intellectual capital simultaneously has a positive effect on firm value. Meanwhile, green innovation has a positive effect on firm value. Then, firm size weakens the moderating effect of green intellectual capital on firm value.